Metastasis from a primary hepatic angiosarcoma to the colon: A case report and literature review - Mokutani, Yukako; Hata, Taishi; Miyake, Yuichiro; Kuroda, Hideki; Takahashi, Hidekazu; Haraguchi, Naotsugu; Nishimura, Junichi; Mizushima, Tsunekazu; Yamamoto, Hirofumi; Doki, Yuichiro; Mori, Masaki (Oncology letters, 2017)
Primary hepatic angiosarcoma is a rare type of tumor with a poor prognosis. To the best of our knowledge, curative surgery of a metastatic gastrointestinal angiosarcoma from a hepatic angiosarcoma has not been reported previously. In the present report, a case of colonic metastasis from a primary hepatic angiosarcoma is discussed. A rapidly growing mass was identified in the liver of an 84-year-old Japanese male who underwent a subsegmentectomy of the liver. Microscopic examination determined that the mass was an angiosarcoma composed of sheets of spindle cells. Immunohistochemical studies confirmed the diagnosis with positive CD31 staining, which indicated the endothelial nature of the malignancy. A total of 14 months following surgery, the patient did not exhibit any symptoms; however, follow-up positron emission tomography and computed tomography images revealed a mass in the cecum. The patient underwent an ileocolectomy, and the microscopic and immunohistochemical findings indicated that the mass was a metastasized colorectal angiosarcoma. At a 4-year post-surgery follow-up appointment the patient was alive with no evidence of recurrence or metastasis.